STATUS OF CORAL REEFS IN THE LEMBEH STRAITS AND ADJACENT WATER, NORTH SULAWESI - Suharsono, - (Research Center for Oceanography - Indonesian Institute of Sciences (LIPI), 2012)
Lembeh reefs and its water surrounding are among the richest and most diverse in marine biota in Indonesia. The biota and reefs in this area have an important contribution to the provinceÃ¢â¬â¢s economy in the form of tourisms and fishery activities. An inventory using line intercept transect and free collection on the coral diversity has been conducted in four different locations showed that live coral cover ranging from 12.2Ã¢â¬â60.7% while sand rubble ranged from 4.67 to 78.67%. Among the life form categories, sponge dominated other biota with 0.47Ã¢â¬â21.97% coverage. Macro algae and turf algae cover were low at all sites, with average less than 2.07%. A total of 193 corals species belonging to 68 genera were recognized from this area. The differences among sites may be consequences of water quality, habitat variability and condition of the land base activities. Water turbidity in the coastal area of Kema was high due to the effects of water discharge from river mouth. Further, poor land management, development of port and human settlement leading to sedimentation, water pollution and poor water quality, remain the primary causes of reefs declines. Busy harbor and local sea transportation will be the major cause of coral reef degradation in the near future. There is a need to increase awareness of local people about the important of coral reefs and to develop management and conservation efforts involving scientists, academe and tourist operators. In addition, it is a need to strengthen the capabilities and capacities of institutions that concern reef management and enforce legislation.ÃÂ